From Patronage to a Professional State : Bolivia Institutional and Governance Review, Volume 1. Main Report - World Bank (Washington, DC, 2013)
The study, an institutional, and governance review of Bolivia, describes the transformation of the country's political economy as of the 1980s, the aim for consistent macroeconomic stability, and, the consolidation of the democratic political regime. However, despite a number of bold reforms to develop market-oriented systems, and in contrast with government efforts, the quality of public services remained low. Namely, because public sector reforms were not implemented, and because of symptomatic institutional weaknesses; for although assistance was provided to modernize the civil service, and improve public administration, the lack of government commitment to a changing program focus, precluded noticeable results. The current reform agenda has identified the need for state modernization, governance and accountability, and judicial reform, addressed within the National Integrity Plan, to combat corruption, and other symptoms of public sector dysfunction. The study presents a blunt vision of Bolivian public administration, through the absence of a functioning bureaucracy, reviewing the legal framework and organizational structure, with an emphasis on the "informality" of public administration, - a challenge for institutional development. But the deeper causes of poor public sector performance, lie on the patrimonial dynamics of party politics. Recommendations include parallel advances between public, and market sector reforms, reliable external controls, and strengthened capacity of the public sector.